2017
DOI: 10.1097/nmd.0000000000000583
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcome in the Middle Course of Bipolar Disorder

Abstract: The aim of this study was to assess the long-term functional outcome of patients with bipolar disorder (BD). At baseline and after a follow-up period of at least 48 months, three measures of functioning were administered: psychosocial functioning (GAF), employment status (full-time, part-time, and unemployment/disability), and a self-reported measure of functional recovery. At baseline, patients with more than five previous affective episodes exhibited poorer outcomes on all measures of functioning than patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…The stability found in the neurocognitive impairment is in accordance with the results obtained in most longitudinal studies which have examined the course of neurocognitive function both in patients with BD [31,[54][55][56], and patients with SZ [57][58][59]. Likewise, in accordance with our results, other authors could not establish a progressive course of the psychosocial impairment in patients with BD [35], or in patients with SZ [60,61]. In this regard, although it cannot be dismissed the possibility of a subset of patients with BD with a progressive course [39], our results suggest that the presence of a history of psychotic symptoms is not associated with a progression of the neurocognitive or psychosocial impairment.…”
Section: Discussionsupporting
confidence: 93%
“…The stability found in the neurocognitive impairment is in accordance with the results obtained in most longitudinal studies which have examined the course of neurocognitive function both in patients with BD [31,[54][55][56], and patients with SZ [57][58][59]. Likewise, in accordance with our results, other authors could not establish a progressive course of the psychosocial impairment in patients with BD [35], or in patients with SZ [60,61]. In this regard, although it cannot be dismissed the possibility of a subset of patients with BD with a progressive course [39], our results suggest that the presence of a history of psychotic symptoms is not associated with a progression of the neurocognitive or psychosocial impairment.…”
Section: Discussionsupporting
confidence: 93%
“…Table lists the 24 scales and functional domains addressed by each. Three scales, the GAF, the LGOS, and the Functional Recovery Self‐assessment (a 1‐question [yes/no] self‐assessment) only provide a global assessment of general functioning, whereas the remaining 21 scales provide assessments related to specific domains such as work/education, residential life, social relationships, family relationships, psychological health, autonomy and performance, and recreation. Thirteen instruments include an occupational functioning domain.…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen longitudinal observational studies met the inclusion criteria. Five studies (all published between 2011 and 2016) only used the FAST scale; two (published between 2010 and 2013) used both the GAF and the FAST; three (published between 2003 and 2017) used the GAF along with functional scales other than FAST; and five (published between 2005 and 2010) used scales other than the GAF and the FAST to assess functioning …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have shown evidence that worsening of functional outcome throughout the course of BD is linked to neuroprogression [64][65][66][67][68]. Additionally, Martino et al [69] a longitudinal study showed that BD patients with more than five previous affective episodes at baseline exhibited poorer outcomes on all measures of functioning than patients with less than five previous episodes; however, during the follow-up period of the study, the level of functioning remained stable in BD patients. Despite the fact that the functional outcome is highly variable among individuals with BD [70], difficulties with activities of daily living, living conditions, occupational/recreational activities, and relationships have been associated with increased risks of mortality in general population samples and other patient groups [71][72][73][74].…”
Section: Discussionmentioning
confidence: 98%